Posterior malleolar fracture morphology determines outcome in rotational type ankle fractures. Issue 7 (July 2019) - Blom, R.P.; Meijer, D.T.; de Muinck Keizer, R-J.O.; Stufkens, S.A.S.; Sierevelt, I.N.; Schepers, T.; Kerkhoffs, G.M.M.J.; Goslings, J.C.; Doornberg, J.N.
Highlights: Posterior malleolar fracture morphology evaluated with computed tomography and not with - unreliable - plain radiographs. Posterior malleolar fracture morphology determines outcome in rotational type ankle fractures. Posterior malleolar ankle fractures with medial extension are associated with significantly poorer functional outcome scores at two years postoperative. Undertake computed tomography imaging when a posterior malleolar ankle fracture is expected. Base treatment decision not on the fracture-fragment-size threshold, but merely on fracture morphology and fragment pathoanatomy. Abstract: Introduction: Rotational type ankle fractures with a concomitant fracture of the posterior malleolus are associated with a poorer clinical outcome as compared to ankle fractures without. However, clinical implications of posterior malleolar (PM) fracture morphology and pattern have yet to be established. Many studies on this subject report on fragment size, rather than fracture morphology based on computed tomography (CT). The overall purpose of the current study was to elucidate the correlation of PM fracture morphology and functional outcome, assessed with CT imaging and not with –unreliable- plain radiographs. Methods: Between January 2010 and May 2014, 194 patients with an operatively (ORIF) treated ankle fracture, were prospectively included in the randomized clinical EF3X-trial at our Level-I trauma center. The current study retrospectively included 73 patients with rotational type ankle fractures and concomitant fractures of the posterior malleolus. According to the CT-based Haraguchi fracture morphology, all patients were divided into three groups: 20 Type I (large posterolateral-oblique), 21 Type II (transverse medial-extension) and 32 Type III (small-shell fragment). At 12 weeks, 1 year and 2 years postoperatively the Foot and Ankle Outcome Scores( FAOS) and SF-36 scores were obtained, with the FAOS domain scores at two years postoperative as primary study outcome. Statistical analysis included a multivariate regression and secondary a mixed model analysis. Results: Haraguchi Type II PM ankle fractures demonstrated significantly poorer outcome scores at two years follow-up compared to Haraguchi Types I and III. Mean FAOS domain scores at two years follow-up showed to be significantly worse in Haraguchi Type II as compared to Type III, respectively: Symptoms 48.2 versus 61.7 (p = 0.03), Pain 58.5 versus 84.4 (p < 0.01), Activities of Daily Living (ADL) 64.1 versus 90.5 (p < 0.01). Conclusion: Posterior malleolar ankle fractures with medial extension of the fracture line (i.e. Haraguchi Type II) are associated with significantly poorer functional outcomes. The current dogma to fix PM fractures that involve at least 25–33% of the tibial plafond may be challenged, as posterior malleolar fracture pattern and morphology - rather than fragment size - seem to determine outcome.